COMPARATIVE ANALYSIS BETWEEN INDIAN AND AMERICAN CULTURE IN THE NOVEL THE NAMESAKE BY JHUMPA LAHIRI - Ningsih, Ayu Melati; Irawan, Fadhilah; Sultan Nico, Rifky; Fahreza, Mas Andika; Raudah, Raudah (Fakultas Sastra UMN AL Washliyah, 2024)
The novel The Namesake by JhumpaLahiri tells the story of Gogol Ganguli, an American-Indian man who was born in Calcutta, India, and raised in the United States. The novel explores themes of identity, culture, and family. In this novel, American and Indian cultures are depicted in contrast. American culture is characterized by individualism, freedom, and pragmatism. Meanwhile, Indian culture is characterized by collectivism, tradition and spirituality. The aim of the comparative cultural analysis in this novel is to explore and unravel the complex cultural interactions depicted in the narrative. Through this analysis, the researcher aims to uncover the complexities and nuances of the journey of the protagonist, Gogol Ganguli, as he adapts between his Indian heritage and the American lifestyle.